2021
DOI: 10.1177/17455065211060624
|View full text |Cite
|
Sign up to set email alerts
|

Contextual risk and psychosocial profiles of opioid-using mothers: A mixed-methods study

Abstract: Introduction: There is an increase in cases of mothers using opioids during pregnancy in the United States but research investigating mothers’ psychosocial environments along with individual variability among this high-risk group of women is scarce. Methods: This mixed-methods study aims to examine the complex interplay of contextual risks and experiences of opioid-using mothers. A sample of 50 opioid-using biological mothers of infants diagnosed with neonatal opioid withdrawal syndrome (NOWS) were studied usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 49 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…ACEs Among People with Current Opioid Use-Related Behaviors. Five studies measured current opioid use-related behaviors (Beltran-Arzate et al, 2021;Guarino et al, 2021;Sansone et al, 2009;Stein et al, 2017;Swedo et al, 2020). Three of these studies conducted statistical analyses, and the results revealed significant associations between ACEs and opioid use-related behaviors.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…ACEs Among People with Current Opioid Use-Related Behaviors. Five studies measured current opioid use-related behaviors (Beltran-Arzate et al, 2021;Guarino et al, 2021;Sansone et al, 2009;Stein et al, 2017;Swedo et al, 2020). Three of these studies conducted statistical analyses, and the results revealed significant associations between ACEs and opioid use-related behaviors.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…The nine treatment centers in the selected studies also represented different settings: five studies were from urban clinics (Carr et al, 2021; Conroy et al, 2009; Gannon et al, 2017; Heffernan et al, 2000; Stein et al, 2017); two studies were from rural clinics (Derefinko et al, 2019; Winstanley et al, 2020); one study was conducted among homeless people receiving care from a mobile treatment facility (O’Gurek et al, 2021); and one study did not specify the treatment setting (Sansone et al, 2009). One article was a case-control study (Conroy et al, 2009), whereas all other articles ( n = 19) were cross-sectional studies, including one mixed method study (Beltran-Arzate et al, 2021). The majority of the studies ( n = 17) were conducted in the United States; one study was from China (Lei et al, 2018), one was from Australia (Conroy et al, 2009), and one was from Nigeria (Onu et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations